Strategic advertisement with externalities: a new dynamic approach - Reinoud Joosten (Max Planck Institute of Economics, 2007)
We model and analyze strategic interaction over time in a duopolis-tic market. Each period the firms independently and simultaneously choose whether to advertise or not. Advertising increases the own immediate sales, but may also cause an externality, e.g., increase or decrease the immediate sales of the other firm ceteris paribus. There exists also an effect of past advertisement efforts on current sales. The 'market potential' of each firm is determined by its own but also by its opponent's past efforts. A higher effort of either firm leads to an increase of the market potential, however the impact of the own past efforts is always stronger than the impact of the opponent's past efforts. How much of the market potential materializes as immediate sales, then depends on the current advertisement decisions. We determine feasible rewards and (subgame perfect) equilibria for the limiting average reward criterion using methods inspired by the repeated-games literature. Uniqueness of equilibrium is by no means guaranteed, but Pareto efficiency may serve very well as a refinement criterion for wide ranges of the advertisement costs.
Keywords: C72; C73; L13; M31; M37; 330; advertising; externalities; average rewards; equilibria; Werbeplanung; Duopol; Externer Effekt; Nichtkooperatives Spiel; Dynamisches Spiel; Gleichgewicht; Theorie